2018
DOI: 10.3748/wjg.v24.i9.1035
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of inflammatory bowel disease in children under six years of age in China

Abstract: AIMTo analyze clinical differences between monogenic and nonmonogenic very-early-onset inflammatory bowel disease (VEO-IBD) and to characterize monogenic IBD phenotypically and genotypically via genetic testing.METHODSA retrospective analysis of children aged 0 to 6 years diagnosed with VEO-IBD in a tertiary hospital in southern China from 2005 to 2017 was performed. Clinical data for VEO-IBD patients were collected, and genetic characteristics were analyzed using whole exome sequencing or target gene panel se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…In our study, patients with EO‐CD, especially with VEO‐CD, had lower remission rates but higher mortality rates than those with LO‐CD. There are limited studies on mortality in patients with PIBD . We found that the Chinese group had a higher mortality rate than the western European group.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In our study, patients with EO‐CD, especially with VEO‐CD, had lower remission rates but higher mortality rates than those with LO‐CD. There are limited studies on mortality in patients with PIBD . We found that the Chinese group had a higher mortality rate than the western European group.…”
Section: Discussionmentioning
confidence: 61%
“…There are limited studies on mortality in patients with PIBD. 11,13,31,32 We found that the Chinese group had a higher mortality rate than the western European group. One pediatric study has focused on mortality in patients diagnosed at childhood with CD.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The incidence of IBD in industrialized countries is higher than that in developing countries; however, overwhelming data suggest that its prevalence is increasing worldwide in both adult[ 3 ] and pediatric populations[ 4 ] and that its distribution is uneven among regions[ 5 ]. Many explanations have been proposed, but the hypothesis that exposure to environmental and genetic factors is a fundamental contributor to the development of IBD has been challenged by several new observations[ 6 - 10 ]. Whether the etiology of pediatric-onset IBD differs from that of adult-onset IBD remains unknown[ 11 ].…”
Section: Introductionmentioning
confidence: 99%